Functional range of motion of the cervical spine in cervical fusion patients during activities of daily living. (May 2023) - Riffitts, Michelle; Oh, Adrianna; Alemu, Abenezer; Patel, Vikrant; Smith, Clair N.; Murati, Sebastian; Bailes, Anna; Allen, Marcus; Dombrowski, Malcom; Lee, Joon Y.; Donaldson, William F.; Clark, William W.; et al.
Abstract: Following cervical spine fusion there is a reduction in maximum range of motion (ROM) but how this impacts activity of daily living (ADLs) and quality of life is unknown. This study's purpose is to quantify maximum and functional cervical spine ROM in patients with multi-level cervical fusion (>3 levels) compared to controls during ADLs and to correlate functional range of motion with scores from patient reported outcomes measures (PROs) including the Comparative Pain Scale (CPS), Fear Avoidance Belief Questionnaire (FABQ), and Neck Disability Index (NDI). An inertial measurement unit (IMU) system quantified ROM during ADLs in the extension/flexion, lateral bending, and axial rotation directions of motion. The reliability of this system was compared to standard optical motion tracking. Fourteen participants (8 females, age = 60.0 years (18.7) (median, (interquartile range)) with a history of multi-level cervical fusion (years post-op 0.9 (0.7)) were compared to 16 controls (13 females, age = 52.1 years (15.8)). PROs were collected for each participant. Fusion participants had significantly decreased maximum ROM in all directions of motion. Fusion participants had decreased ROM for some ADLs (backing up a car, using a phone, donning socks, negotiating stairs). CPS, FABQ, and NDI scores were significantly increased in fusion participants. Reductions in two activities (backing up a car, stair negotiation) correlated with a combination of increased PRO scores. Cervical fusion decreases maximum ROM and is correlated with increased PROs in some ADLs, however there is minimal impact on functional ROM. Investigation into velocity and acceleration may yield categorization of pathologic movement.